2022
DOI: 10.1042/cs20220479
|View full text |Cite
|
Sign up to set email alerts
|

Human placental lipid content and lipid metabolic enzyme abundance in obesity and across gestation

Abstract: Changes in placental lipid metabolism influence the delivery of lipids critical for fetal development and fetal requirements for lipids change across gestation. We hypothesized that placental lipid content and metabolic enzyme protein levels increase across gestation and are elevated in obesity. Placentas (4-40 weeks gestation) were collected from control (body mass index, BMI 18.5-24.9, n=37) and obese (BMI>30, n=19) pregnant women. Trophoblast villous tissue was homogenized and subjected to LC-MS/MS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…After electrophoresis and transfer onto a PVDF membrane (Bio-Rad Laboratories Inc.), we stained for total protein using Amido Black Stain (Sigma-Aldrich). Incubation of primary antibody LysoPhosphatidylCholine Acyl Transferase 4 (LPCAT4), PhosphoLipase A 2 Group IVC (PLA 2 G4C or iPLA 2 ) and 1-acylglycerol-3-phosphate O-acyltransferase 4 (AGPAT4) was carried out overnight at 4 °C (details on primary antibodies are provided in Additional file 1 : Table S2), and secondary antibody (peroxidase labeled anti-Rabbit IgG, diluted 1:3000, Cell Signaling Technology (Danvers, MA)) for 1 h at room temperature as previously depicted [ 35 ]. Immunolabeling was made visible with SuperSignal West Pico Plus detection solution (Thermo Scientific) in a G:Box ChemiXL1.4 (SynGene, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After electrophoresis and transfer onto a PVDF membrane (Bio-Rad Laboratories Inc.), we stained for total protein using Amido Black Stain (Sigma-Aldrich). Incubation of primary antibody LysoPhosphatidylCholine Acyl Transferase 4 (LPCAT4), PhosphoLipase A 2 Group IVC (PLA 2 G4C or iPLA 2 ) and 1-acylglycerol-3-phosphate O-acyltransferase 4 (AGPAT4) was carried out overnight at 4 °C (details on primary antibodies are provided in Additional file 1 : Table S2), and secondary antibody (peroxidase labeled anti-Rabbit IgG, diluted 1:3000, Cell Signaling Technology (Danvers, MA)) for 1 h at room temperature as previously depicted [ 35 ]. Immunolabeling was made visible with SuperSignal West Pico Plus detection solution (Thermo Scientific) in a G:Box ChemiXL1.4 (SynGene, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…One study has observed increased plasma ether PC containing DHA (PC O-16:0_22:6) in healthy women at 26–28 weeks of pregnancy compared to postnatal 4–5 years after delivery [ 18 ]. We have recently identified some ether linked phospholipid species in human placenta across gestation and found PE containing LCPUFA, such as PE O-16:1_22:6 and PE O-16:1_20:4, are enhanced in the third trimester compared to the first and second trimesters [ 35 ]. These data suggest a potential implication of those phospholipids in the placental LCPUFA metabolism and transfer to the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Science , Bidne et al have been able to surmount this challenge to examine human placentas and cord blood ranging from 4 to 40 weeks gestation [ 23 ]. Their study builds upon previous work detailing placental nutrient transporters across gestation [ 24 ] by quantifying lipid fractions, transporters, and metabolic pathways in first, second, and third trimester placenta, then comparing these levels between obese and non-obese pregnant women.…”
mentioning
confidence: 99%
“…Acyl-transferase enzymes like glycerol-3-phosphate acyltransferase (GPAT) and 1-acylglycerol-3-phosphate-O-acyltransferases (AGPAT2 and AGPAT4) in the Kennedy Pathway and phospholipase A2 (PLA2G4c) and lysophosphatidylcholine acyltransferase (LPCAT4) in the Lands’ cycle remodel the fatty acid species being transported to the fetus. These elements of lipid metabolism in the placenta can be studied over gestation as well as between control and obese pregnancies to determine the mechanisms driving this important element of fuel transport, as demonstrated by Bidne et al [ 23 ] in this issue of Clinical Science . Created with BioRender.com.…”
mentioning
confidence: 99%
See 1 more Smart Citation